Thymidine kinase 1 concentration and activity in metastatic breast cancer under CDK4/6 inhibitor therapy - Stefanos Ioannis Moukas; Merle Dohn; Catrin Lehnerdt; Anja Welt; Hans-Christian Kolberg; Oliver Hoffmann; Rainer Kimmig; Sabine Kasimir-Bauer; Corinna Keup (Scientific Reports)
Abstract We investigated whether TK1 concentration or activity in the blood, drawn at baseline and under therapy, might have value for therapy management in 110 hormone receptor-positive (HR+), HER2-negative (HER2-) metastatic breast cancer (mBC) patients treated with CDK4/6 inhibitors (CDK4/6i) and/or endocrine therapy (ET). TK1 concentration and activity were not significantly correlated with each other in matched samples. In the CDK4/6i cohort at baseline, high TK1 concentration and activity were significantly associated with a decreased PFS and primary resistance. Longitudinal sampling revealed a higher variability of TK1 concentration under therapy compared to TK1 activity that was reduced during therapy. Elevated TK1 activity after six months of CDK4/6i and an increase in TK1 concentration from baseline to six months under CDK4/6i significantly correlated with a decreased PFS. These results indicate a possible value of TK1 concentration and activity before and during CDK4/6i for HR+/HER2- mBC patients to guide treatment that warrants further investigation.